2018
DOI: 10.1051/matecconf/201818801021
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of the effect of preform length for the fabrication of 1.5Lt PET bottle through the injection stretch blow molding process

Abstract: Abstract. This study carries the numerical effort for the investigation of effect of preform length on the final product wall thickness distribution. For the investigation, three different preform length cases were taken under consideration. Preform A, preform B and preform C of length 144.75mm, 165.7mm and 186.65mm respectively. All the preforms were stretched up to a same critical point respect to mold length so that the axial deformation during blowing was fair for all the preform cases. Blowing conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Lontos and Gregoriou [98] considered three different preform lengths in order to explore the influence of preform length on the wall thickness distribution of the final product and found that the bottom area of the bottle made of the longer preform length was thicker, which enhanced the overall stability. In order to minimize the wall thickness and reduce the use of PET, Tan et al [99] used ANSYS Polyflow to evaluate the wall thickness distribution of PET bottles with different diameters of initial bottle blanks and determined that the allowable wall thickness of preforms with at least 6 mm diameter can be 1.3 mm.…”
Section: Single Optimizationmentioning
confidence: 99%
“…Lontos and Gregoriou [98] considered three different preform lengths in order to explore the influence of preform length on the wall thickness distribution of the final product and found that the bottom area of the bottle made of the longer preform length was thicker, which enhanced the overall stability. In order to minimize the wall thickness and reduce the use of PET, Tan et al [99] used ANSYS Polyflow to evaluate the wall thickness distribution of PET bottles with different diameters of initial bottle blanks and determined that the allowable wall thickness of preforms with at least 6 mm diameter can be 1.3 mm.…”
Section: Single Optimizationmentioning
confidence: 99%
“…The aim of numerical simulation is to improve accuracy and predictability to efficiently assist in the design of polymer parts. There are many computational models to predict the parameters and results of stretching blow molding [2][3][4][5][6][7]. For example, Lee and Soh used the finite element method (FEM) optimization to define the optimal profile thickness of the preform for a blow-molded part and then presented the wall thickness distribution requirements [7].…”
Section: Introductionmentioning
confidence: 99%